The Competency of Post-Graduate Students of English at UNIB Academic Year 2017-2018 in Identifying Intrinsic Elements of The Short Story of A Rose for Emily (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The aim of this study is to determine the competency of post-graduate students of English Language Faculty UNIB academic year 2017-2018 in identifying intrinsic elements of the short story ‘A Rose for Emily’. The method used on this research is descriptive qualitative method. The research was conducted in May - June 2018 and the instruments used were essay tests. The results showed that the average score of competency was 64.68. The percentage of students who got the highest score, A is 18.75%, for B score is 18.75%, the C score is 43.75% and for the E score is 6.25%. From this study, it concludes that the competency of post-graduate students of English Language Faculty UNIB academic year 2017-2018 in identifying intrinsic elements of the short story ‘A Rose for Emily’ is rather good although there are some other aspects of competency that can be used optimally.